THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY GOAL, CORPORATE SOCIAL ISSUE, AND CORPORATE RELATION PROGRAM OF PT. SEMEN GRESIK TO SOCIAL WELFARE - ROSYIDI, AMIRUL AFFAN (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
Nowadays, companies are increasingly developed, which is at the same time increasing the social gap and the surrounding environmental damage. Therefore, it is urgent to increase the awareness to reduce these negative impacts through Corporate Social Responsibility of the related companies. The objective of this study is to determine the effect of variables corporate social responsibility to social welfare around Gresik by analyzing the influence of CSR variables consisting of items: CSR goals, corporate social issues, and corporate programs related to community well-being in Gresik. The sample of the study is selected using purposive sampling technique with 59 respondents who receive assistance from PT Semen Gresik CSR. To collect the data, survey methods is used in the form of explanatory research. The primary research data is questionnaires, while the secondary data are related literature, internet sources, and interviews. The collected then is sort and analyzed using a Likert scale, while test the validity and reliability is conducted using statistical crosstabs by SPSS 16.0 software. Based on multiple linear regression analysis the results using the t test, it can be concluded that the corporate variables related programs partially affect the social live welfare. While, based on the results of the standardized Beta Coefficients respectively, it is revealed that corporate variables related programs pose dominant influence on the welfare of the community Gresik. So, the result is from Variabel CSR (Corporate Social Responsibility Goal, Corporate Social Issue, Corporate Related Program) does not have significance effect to social live welfare around PT Semen Gresik.. Keywords; CSR goals,Corporate Social Issue, Corporate Relation Program, Social Welfare